Non-linear relationship between albumin-corrected calcium and 30-day in-hospital mortality in ICU patients: A multicenter retrospective cohort study - Qin, Xun; Cen, Ji; Hu, Haofei; Chen, Xinglin; Wei, Zhe; Wan, Qijun; Cao, Rong (Frontiers in Endocrinology, 2022)
Objective: Albumin-corrected calcium is usually calculated to reflect the real serum calcium level of the whole body by physicians. However, studies on the association between albumin-corrected calcium and 30days in-hospital mortality in ICU patients are rare. The purpose of our study was to explore the association between baseline albumin-corrected calcium and 30days in-hospital mortality in the American ICU population. Methods:A muti-center retrospective cohort study of 102245 ICU patients in the eICU-CRD v2.0 from the USA during 2014–2015 was performed. The average age was 63.7 ± 16.9 years, of which 55313 (53.7%) was male and 47758 (46.3%) was female. The association between albumin-corrected calcium and 30days in-hospital mortality was analyzed by cox proportional-hazards regression, smooth curve ftting, piece-wise linear regression, subgroup analyses, and a series of sensitivity analyses. Results: We found that among calcium abnormalities ICU patients, more than 95% were mild hypocalcemia or mild hypercalcemia. The risk of 30days In- hospital mortality will increase 10% in ≥7.5- < 8.5mg/dl subgroup (OR=1.1, 95% CI 1.0–1.3) or 20% in ≥10.3-< 12mg/dl subgroup(OR=1.2, 95% CI 1.1–1.3) when albumin-corrected calcium level increase 1mg/dl. Additionally, the relationship between albumin-corrected calcium and 30days In- hospital mortality was U-shaped, the inflection point was 8.9mg/dl (log likelihood ratio test P =0.005). And finally, after a series of sensitivity analysis, we found that the relationship between albumin-corrected calcium and 30days In- hospital mortality remained significant. Conclusion: In a large nationally representative cohort of ICU patients, abnormalities in albumin-corrected calcium, particularly slightly hypocalcemia or slightly hypercalcemia, were associated with increased 30days In- hospital mortality risk. And yet, the findings in this study need to be further confirmed by prospective studies.